Jaran Kepang Tradition in Bandar Klippa Village: Antropolinguistic Study - Sri Permana Dewi; Robert Sibarani; Pujiati Pujiati (Budapest International Research and Critics University, 2022)
This study examines performance, indexicality and participants in TJK. This study uses a qualitative descriptive approach. The theory used to analyze this study is the Duranti concept. The data in this study were obtained from observations, interviews and documentation from the time the TJK took place until it was finished. Data collection uses documentation techniques, namely the retrieval of data obtained through direct recording which includes three basic dimensions, namely space, actors and activities. Two additional dimensions are objects and feelings. The data analysis in this study uses the Miles & Huberman interactive analysis model. The results showed that the performance in the TJK was divided into: 1) before the TJK performance, 2) during the TJK, and 3) after the TJK took place.